A new species and new records of Pseudocephennium Reitter in Venezuela, with notes on movable endophallic structures (Coleoptera: Staphylinidae: Scydmaeninae) - Jałoszyński, Paweł (Zootaxa, 2016)
Pseudocephennium auriculatum sp. n. is described, based on a male specimen collected in north-western Venezuela. New findings of Pseudocephennium maximum Jałoszyński and P. araguanum Jałoszyński, so far known only from holotypes, are reported. The aedeagi of newly found specimens have the endophallic structures extruded to various extent which makes it possible to identify movable components of the internal aedeagal armature.